사계성 딸기 ‘강하’ 육성 - 이종남(Jong Nam Lee); 이준구(Jun Gu Lee); 이응호(Eung Ho Lee); 김혜진(Hye Jin Kim); 장석우(Suk Woo Jang) (Weon'ye gwahag gi'sulji, 2010)
'Gangha' is new strawberry ($Fragaria{×}ananassa$ Duch.) cultivar, which was released by National Institute of Highland Agriculture, RDA, in 2008. In 2004, this cultivar was originated from a cross between 'Samahberi' and 'Elan' and showed excellent ever-bearing characteristics including continuous flowering habit, high yield under long-day and high temperature condition. It was named 'Saebong No.2' after examining its characteristic and productivity in summer culture from 2006 to 2007. Again, after two regional adaptability tests in 2008, 'Gangha' was selected as an elite cultivar. The general characteristics of 'Gangha' include semi-spreading type, middle vigor, elliptic leaf, and long cluster in growth. The fruit shape is oval and fruit color is red. Fruit quality had 1ow activity, hardness but high soluble solids contents. This average fruit weight of 'Gangha' is about 12.0 g and the marketable yield is relatively high because of more flower cluster appearance. It is resistant against powdery mildew, anthracnose, and fusarium wilt. 'Gangha' is suitable for summer culture using domestic consumption because it is shows continuous flowering habit, high yield, and fruit quality under long-day and high temperature condition. '강하(Gangha)'는 2004년 '섬머베리(Samahberi)' 품종을 모본으로 하고 '엘란(Elan)' 품종을 부본으로 교배하여 고온 장일 하에서 화방이 계속 출현되고, 높은 수량성을 가진 우수한 사계성 개체를 선발한 것이다. 고랭지의 여름재배 작형에서 2006년 생산력 검정, 2007년 특성검정을 거쳐 '새봉 2호'로 계통명을 부여하였고, 2008년 2지역에서 적응성 시험 거쳐 '강하'로 명명하였다. '강하'의 주요특성은 초형이 반개장형으로 초세가 중정도이고 엽형은 타원형이고 화방 길이가 길다. 과형은 난원형이며, 과색은 붉은색을 나타낸다. '강하'는 산도와 경도는 낮지만 당도는 높다. 평균과중이 12.0g의 중과이고 화방이 많이 출현되는 다수성품종이다. 병해저항성은 흰가루병, 탄저병, 시듦병에 강하다. '강하'는 고온장일 하에서 화아분화되고, 과실품질과 수량성이 높아 고랭지대에서 내수용 여름재배에 적합하다.